-25x-13=

Simple and best practice solution for -25x-13= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25x-13= equation:


Simplifying
-25x + -13 = 0

Reorder the terms:
-13 + -25x = 0

Solving
-13 + -25x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + -25x = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -25x = 0 + 13
-25x = 0 + 13

Combine like terms: 0 + 13 = 13
-25x = 13

Divide each side by '-25'.
x = -0.52

Simplifying
x = -0.52

See similar equations:

| 8.3(x-31)=-37.35 | | 2z^2+7z+5=6z^2 | | (logx)6561=8 | | 9x+18=5x+38 | | x+4(-1)=8 | | 7x-4(-2x+7)=-193 | | X+7=3(x+7)-19 | | R=176-0.8x | | -4+(-2)x-3= | | 14m-32=22 | | 15x^2-165x+630=0 | | x+2+x+2+x+2=36 | | X^2=1966 | | -16x^2+150x-3=0 | | 5x^2-12=-8x | | 8(x+7)+6=8.6x-6 | | 5w^2-60=0 | | 7.3x+1.8=1.5+4(x-6.6) | | 9x^2-140x+528=0 | | 9x-2=9(x-3) | | 0=112t-16t^2 | | 16x^2-35x+80=0 | | 2=55t-5t^2 | | 4.1x+7=-2+9.6(x-9) | | x=3xd-21 | | 3absx-4=10 | | 5x-2(-3x-8)=-98 | | -4y+12=-2(4y-6) | | 4xp+6= | | -2x-1-4x=2x+2-5x-15 | | 9.3(x+6)+4=8 | | -8-13=6x+17-5x |

Equations solver categories